Studies on the Semen quality of different Veterinary Institutions - THAKUR, SANDEEP; SINGH, MADHUMEET; VASISHTA, N K (The Indian Journal of Animal Reproduction, 2023)
Twenty frozen semen straws of Jersey and IO from Jersey X Red Sindhi crossbred bulls procured from semen processing Laboratory Palampur were evaluated for quality. Equal number of straws from same bulls and batches were evaluated randomly at different Veterinary institutions of the state. The mean live sperm percentage of Jersey bull semen in frozen thawed straws from semen laboratory was 64-8± 1. 70 as compared to 55. 71±2.43 and 53 . 13±2. 76 in hospitals and dispensaries, respectively. Live sperm percentage of the semen samples from laboratory was significantly higher (p<O.O 1) from those procured from field institutions. Similarly, progressive motility(%) of semen samples from laboratory, hospitals and dispensaries was 57. 93± 1.55, 48.71±2.07 and 46.45±2.48, respectively. The acrosomal integrity(%) of semen laboratory samples was 76.0±0.71 and was significantly better than hospitals (67.45±2.47) and dispensaries (69.59± 1.17). The mean live sperm percentage in crossbred bull semen of semen laboratory was 60.42±2.79 and was better as compared to live percentage of 55.90±2.85 in hospitals and 56.44±2.04 in dispensaries. The progressive motility of samples from semen laboratory was 55.0±2.42. It was 50.90±2.85 and 50.88± 1. 79 in the samples from hospitals and dispensaries, respectively, however, the difference was non significant. The acrosomal integrity of frozen semen straws from crossbred bull semen was 75.42± 1.49, 68. 10±3.46 and 67.88± 1.68, in the samples from laboratory, hospitals and dispensaries, respectively, the difference between samples from laboratory and field institutions was significant (P0.05).